State of the Art: MR Imaging after Knee Cartilage Repair Surgery - Guermazi, Ali; Roemer, Frank; Alizai, Hamza; Winalski, Carl S.; Welsch, Goetz; Brittberg, Mats; Trattnig, Siegfried (Radiology, 2015)
Cartilage injuries are common, especially in athletes. Because these injuries frequently affect young patients, and they have the potential to progress to osteoarthritis, treatment to alleviate symptoms and delay joint degeneration is warranted. A number of surgical techniques are available to treat focal chondral defects, including marrow stimulation, osteochondral auto- and allografting, and autologous chondrocyte implantation. Although arthroscopy is considered the standard of reference for the evaluation of cartilage before and after repair, it is invasive with associated morbidity and cannot adequately depict the deep cartilage layer and underlying bone. Magnetic resonance (MR) imaging provides unparalleled noninvasive assessment of the repair site and all other joint tissues. MR observation of cartilage repair tissue is a well-established semiquantitative scoring system for repair tissue that has primarily been used in clinical research studies. The cartilage repair osteoarthritis knee score (CROAKS) optimizes comprehensive morphologic assessment of the knee joint after cartilage repair. Furthermore, quantitative, compositional MR imaging measurements (eg, T2, T2*, T1?), delayed gadolinium-enhanced MR imaging of cartilage (dGEMRIC), and sodium imaging are available for biochemical assessment. These quantitative MR imaging techniques help assess collagen content and orientation, water content, and glycosaminoglycan and/or proteoglycan content both in the repair tissue as it matures and in the "native" cartilage. In this review, the authors discuss the principles of state-of-the-art morphologic and compositional MR imaging techniques for imaging of cartilage repair and their application to longitudinal studies.
EVALuna2:14523